2011
DOI: 10.4274/tjo.41.02
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Efficacy of Triamcinolone Acetonide and Bevacizumab in a Case with Type 2A Idiopathic Parafoveal Telangiectasia

Abstract: S u m m a r y P u r p o s e :To compare the efficacy of intravitreal triamcinolone acetonide and bevacizumab in the treatment of a case of type 2A idiopathic parafoveal telangiectasia (IPT). Material and Method:A 55-year-old man with complaint of decreased vision in both eyes was diagnosed as type 2A IPT after a complete ophthalmological examination, fundus fluorescein angiography (FA) and optical coherence tomography (OCT). We injected intravitreally 4 mg /0.1 cc of triamcinolone acetonide into the right eye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…12,15,16,17,18,19,20,21,22 In some of these studies, however, the leakage on FA was reported to return to baseline levels during periods without injections. 15,17,20,22 Similarly, though decreases in macular thickness measured by OCT may be detected initially, 12,16,17,18,19,20,21,22,24 studies with long-term follow-up after the final injection reported that OCT findings also returned to baseline. 17,18,20,22 Besides these studies, there are others in which no substantial changes in OCT findings were observed.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…12,15,16,17,18,19,20,21,22 In some of these studies, however, the leakage on FA was reported to return to baseline levels during periods without injections. 15,17,20,22 Similarly, though decreases in macular thickness measured by OCT may be detected initially, 12,16,17,18,19,20,21,22,24 studies with long-term follow-up after the final injection reported that OCT findings also returned to baseline. 17,18,20,22 Besides these studies, there are others in which no substantial changes in OCT findings were observed.…”
Section: Discussionmentioning
confidence: 98%
“…13,14,15 Results concerning visual acuity vary. Some studies show improvements in visual acuity, 12,18,19,20,22 whereas others report no change or even decline over time. 13,14,15,16,20,22,24 Response to treatment varies in terms of disease duration and severity, and degree of neuroretinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations